Cross-Border Acquisitions and Acquirer Firms’ Stock Market Performance: An Analysis of Emerging Markets - Tokbolat, Yerzhan (2014)
While both number and volume of cross-border mergers and acquisitions (CBM&A) from emerging markets have been significantly increasing during the last few decades, the evidence of an impact of the announcements of foreign acquisitions on acquiring firms’ performance remains limited. The main objective of this work is to contribute to the M&A literature by investigating the shareholders’ value implications of 186 CBM&A made by emerging market multinationals (EMMs) from 1993 to 2013. Using an event study methodology we find that, on average, the stock market responds positively to the announcement of acquisitions. Statistically significant positive returns were found for event windows of seven and nine days. Moreover, using a cross-sectional analysis, we find that returns are positively correlated with economic development of a target country, cash form of payment and a crisis year variable indicating deals made in 2007-2008. On the other hand, we find that negative impact on the acquirers’ value is associated with larger size acquisitions and with CBM&A that involve countries with the same language.